LANDASAN HUKUM DAN PERTIMBANGAN HAKIM TEHADAP STATUS ISTRI DALAM PERKARA SUAMI MAFQUD MELALUI PUTUSAN NOMOR 0279Pdt.G2009PA.PAS - Andre Afrilian (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2023)
In Islamic law in some madhabs the disappearance of the husband (mafqud) can be a reason for divorce. Some schools of thought such as Hanabilah and Malikiyah allow the wife to file for divorce if the husband is mafqud and there is no information about his whereabouts for a period of one year as stated by Sayyid Sabiq and Imam Malik. In addition, through positive law, it is regulated in Government Regulation No. 9 of 1975. However, there is a decision in the Pasuruan Religious Court No. 0279/Pdt.G/2009/PA.Pas which grants the divorce of a wife whose husband is mafqud with a period of only four months, so this article tries to examine the reasons why the judge granted the divorce filed by the wife and the legal considerations used as a basis through maslahah mursalah. The research method used in this research is juridical-normative using qualitative analysis and the maslahah mursalah approach. Based on the results of the research, there are several supporting factors the court's basis in granting the decision with the situation that the husband has married another woman without the knowledge of legal wife so that by reviewing the concept of benefit, the lawsuit is granted.